1992
DOI: 10.1007/bf02050332
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of right colon diverticulitis

Abstract: The infrequent occurrence of right colon diverticulitis in the developed West has led to a controversy in the management of this disease. In Singapore, we continued to avoid colectomy whenever possible because this disease is usually nonprogressive. We reviewed 68 patients treated by conservative surgery to evaluate the effectiveness of this treatment policy. Almost 70 percent of our patients were below 40 years of age, and the clinical presentation was indistinguishable from acute appendicitis. Diverticulecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 9 publications
2
36
0
6
Order By: Relevance
“…However, after successful conservative treatment, a recurrence rate of 3.6% to 23.8% has been reported in the literature [5,7,8,20,21,30] . Ngoi et al [31] reported a recurrence rate of 1.5%, but 38% of their patients underwent diverticulectomy. It is interesting to note that in these studies, there was little complicated diverticulitis in recurrent cases: Fang et al [5] reported three complicated cases in 10 recurrences in 42 patients receiving conservative treatments, and Harada et al [30] reported one complicated case in four recurrences in 29 patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, after successful conservative treatment, a recurrence rate of 3.6% to 23.8% has been reported in the literature [5,7,8,20,21,30] . Ngoi et al [31] reported a recurrence rate of 1.5%, but 38% of their patients underwent diverticulectomy. It is interesting to note that in these studies, there was little complicated diverticulitis in recurrent cases: Fang et al [5] reported three complicated cases in 10 recurrences in 42 patients receiving conservative treatments, and Harada et al [30] reported one complicated case in four recurrences in 29 patients.…”
Section: Discussionmentioning
confidence: 97%
“…ha comunicado una mejor respuesta al tratamiento médico que en diverticulitis del colon izquierdo y que la historia natural es benigna a pesar de su evolución 7,9,11 . La recurrencia oscila entre el 10% y el 25% durante seguimientos a 10 años y no se han comunicado complicaciones severas durante las mismas 12,13 .…”
Section: Discussionunclassified
“…For example, a computed tomography (CT) scan may generate confusion between right-sided diverticulitis and carcinoma or severe ischemic colitis [13]. In those patients, the knowledge of right-sided diverticula helps to avoid unnecessary medical and/or surgical approach [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a computed tomography (CT) scan may generate confusion between right-sided diverticulitis and carcinoma or severe ischemic colitis [13]. In those patients, the knowledge of right-sided diverticula helps to avoid unnecessary medical and/or surgical approach [13]. Diverticulosis of the left colon is much more frequent, and the risk of acute diverticulitis occurrence in those patients is about 1/1000 lifetime [8].…”
Section: Introductionmentioning
confidence: 99%